An elderly lady must not be crossed - Tursten, Helene, 1954- (Soho Crime, 2021)
"Just when things have finally cooled down for 88-year-old Maud after the disturbing discovery of a dead body in her apartment in Gothenburg, a couple of detectives return to her doorstep, ruining a perfectly good afternoon. Though Maud deftly dodges their questions with the skill of an Olympic gymnast a fifth of her age, she wonders if suspicion has fallen on her, little old lady that she is. The truth is, ever since Maud was a girl, death has seemed to follow her. In these six interlocking stories, memories of unfortunate incidents from Maud's past keep bubbling to the surface, each triggered by something around her: an image, a word-even a taste. Meanwhile, certain Problems in the present require immediate attention. Luckily, Maud is no stranger to taking matters into her own hands . . . even if it means she has to get a little blood on them in the process"--